Sobre a amorfia (formlessness) em Winnicott e seu papel na simbolização - Abram, Jan (Revista de Psicanálise da SPPA, 2013)
Este ensaio examina o último trabalho de Winnicott no qual ele enfoca os estágios iniciais do desenvolvimento psíquico. Amorfia, relacionada ao conceito anterior de Winnicott de não integração, é um precursor necessário para a integração e o pensamento simbólico. Assim, o sujeito poderia ir da relação com o objeto para o uso do objeto. No derradeiro trabalho de Winnicott ele sugere a noção do pai como objeto inteiro no início. Aqui vou propor a noção de integrado paterno, vinculada ao conceito de o outro do objeto de André Green. Concluo que a noção de Winnicott do pai como objeto inteiro desde o início da vida completa sua matriz teórica, uma vez que inclui a noção de uma dinâmica triádica no estágio mais inicial da vida psíquica. On Winnicott’s area of formlessness and its role in symbolization This essay examines Winnicott’s late work in which he focuses on the earliest stages of psychic development. Formlessness, related to Winnicott’s earlier concept of unintegration, is a necessary precursor to integration and symbolic thinking. Thus the subject could move from object relating to object usage. In Winnicott’s very late work he suggests the notion of the father as a whole object at the beginning. Here, I will propose the notion of a paternal integrate linked with André Green’s concept of the other of the object. I conclude that Winnicott’s notion of the father as whole object from the beginning of life completes his theoretical matrix because it includes the notion of a triadic dynamic at the earliest stage of psychic life. Keywords: formlessness, early psychic development, symbolic thinking, paternal integrate, triadic dynamic, André Green, Winnicott, formlessness, symbolization.